Tingkat Kepuasan Mahasiswa Terhadap Kualitas Pelayanan Angkot di Kota Medan - Siahaan, Reynaldo (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2018)
In general, urban transportation experiences similar problem, which is the low level of public transport occupancy. There are numerous factors that can cause such condition, of which can be summarized in the form of service quality shortcoming. Service quality of such public facility is measured and evaluated based on user experience, and planners utilize it to plan for future improvements. Importance-Performance Analysis is used in this research to identify aspects of service that are expected to be on top of enhancement priority list. Based on 159 students’ responses, it was found that six service criterias are in high-priority-quadrant. These are crowding, sitting comfort, hygiene, driver behavior, driver cleanliness, and security. Specifically, driver behavior aspect is regarded as highly prioritized, whereas on the contrary angkot fare and operating time are considered good enough and thus placed on low-priority list.